Analisis Pengaruh Merjer Terhadap Kinerja Keuangan dan Return Saham"Studi Kasus Merjer Bank Lippo dan Bank Niaga Periode 2002-2009" - , RADEN SATRIO ARIEF PAMBUDI; , Prof. Dr. Mudrajad Kuncoro M.Soc.Sc, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In banking industry, nationally or internationally, merger is one kind of alternative for effective strategy in order to have a healthy and better condition in banking industry of a nation. This merger strategy can be used as a tool to boost the growth and development in a business, so it can increase company market value. The objectives of this research was found the effect of merger on CIMB Niaga financial performance based on CAMEL, and its impact on stock return. To find the impact what factors influencing it, the author used multiple linear regression analysis and paired sample t- test, hypothesis test and classical assumption test methods. The data used in this research were secondary data gathered from Indonesia Bank. The result of this research showed that merger has significant impact toward CAMEL, which means CAMEL better after the merger than before the merger. Merger does not have significant impact toward stock return, evident from the abnormal return that does not have significant differences at the time before and after the merger. CAR, BOPO, RORA, and NIM have significant impact toward net profit margin (NPM). Overall CAMEL proved to affect the ratio of net profit margin (NPM).